2019
DOI: 10.1177/2192568219890292
|View full text |Cite
|
Sign up to set email alerts
|

Does Smoking Status Influence Health-Related Quality of Life Outcome Measures in Patients Undergoing ACDF?

Abstract: Study design: Retrospective comparative study. Objective: Whereas smoking has been shown to affect the fusion rates for patients undergoing an anterior cervical discectomy and fusion (ACDF), the relationship between smoking and health-related quality of life outcome measurements after an ACDF is less clear. The purpose of this study was to evaluate whether smoking negatively affects patient outcomes after an ACDF for cervical degenerative pathology.Methods: Patients with tumor, trauma, infection, and previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
0
14
2
Order By: Relevance
“…The number of patients who underwent reoperation was provided in eight studies 4 , 11 13 , 20 , 41 , 46 , 49 . Significant heterogeneity was observed, and a random-effects model was used (I 2 = 57.7%, p = 0.020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of patients who underwent reoperation was provided in eight studies 4 , 11 13 , 20 , 41 , 46 , 49 . Significant heterogeneity was observed, and a random-effects model was used (I 2 = 57.7%, p = 0.020).…”
Section: Resultsmentioning
confidence: 99%
“…Pooling of the results demonstrated that smokers were more associated with reoperation than nonsmokers (ES = 1.80, 95% CI: 1.06–3.06, p = 0.0029). When performing statistical analysis of Mangan et al 46 , we defined the sum of current and former smokers as the total number of smokers. We then removed Mangan et al, performed a sensitivity analysis, and found that heterogeneity was reduced to 41.4% (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that smoking status negatively impacted the overall clinical outcomes of anterior cervical spine surgery, mainly the recovery of nerve function. However, the effect of smoking on the success rate of fusion is still under debate, although most studies concluded that smoking status did not affect the fusion rate [17,18,20,40]. The effect of smoking on the clinical outcomes of posterior approach cervical surgery remains controversial, with some studies have shown that smoking adversely affects clinical outcomes after posterior cervical fusion [22,41].…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients who underwent reoperation was provided in eight studies 4,[11][12][13]20,42,47,50 . Signi cant heterogeneity was observed, and a randomeffects model was used (I²=58%, p=0.02).…”
Section: Reoperationmentioning
confidence: 99%
“…Pooling of the results demonstrated that the incidence of reoperation in the smoking group was signi cantly higher than that of the non-smoking group (OR=1.94, 95% CI: 1.0-3.80, p=0.05). When performing statistical analysis of Mangan et al 47 , we de ned the sum of current and former smokers as the total number of smokers. We then removed Mangan et al, performed a sensitivity analysis, and found that heterogeneity was reduced to 39% (Fig.…”
Section: Reoperationmentioning
confidence: 99%